The Influence of Science on the Mindset of Indonesian Society: A Case Study of the Acceptance of Technology and Popular Science - Uki, Riyan Setiawan; Maria, Maria; Alam, Nur (Jurnal Penelitian Pendidikan, 2025)
The development of science and technology has significantly transformed the way people think and interact in modern societies, including Indonesia. This study aims to analyze how science influences the mindset of Indonesian society, focusing on the acceptance of technology and popular science. Using a descriptive-empirical approach, this research employs literature review and secondary survey analysis from sources such as OECD PISA (2022), UNESCO Science Report (2023), and BRIN (2023). The findings indicate that Indonesia’s scientific literacy remains below the global average, with cultural and religious factors playing a crucial role in shaping attitudes toward science and technology. Although public perception of science is generally positive, there is a gap between interest and practical engagement, particularly among students. Media exposure and popular science content significantly mediate the formation of scientific attitudes, but low digital literacy often leads to misinformation. The study concludes that the integration of science education with socio-cultural and ethical values is essential to fostering a rational, open-minded, and evidence-based public mindset in Indonesia.